2009
DOI: 10.2139/ssrn.1432550
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Neighborhood Impacts of the Mortgage Assistance Program in Dallas

Abstract: Down-payment or closing cost assistance is a commonly used and effective program in addressing the wealth constraints of underserved homebuyers. This paper estimates the impact of the city of Dallas Mortgage Assistance Program (MAP) on neighborhood home values. We define neighborhoods for each sale based on distance from MAP properties, and estimate the difference-indifference (DID) in home prices between neighborhoods with various numbers of MAP before and after MAP sales. We find that while MAP properties te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Di, Ma, and Murdoch (2007) found that the mortgage default rate and foreclosure rate of MAP were lower than that of subprime loans in Texas—the likely alternative for LMI households. MAP loans also outperformed FHA loans in Texas.…”
Section: Overview Of the City Of Dallas Mapmentioning
confidence: 99%
See 2 more Smart Citations
“…Di, Ma, and Murdoch (2007) found that the mortgage default rate and foreclosure rate of MAP were lower than that of subprime loans in Texas—the likely alternative for LMI households. MAP loans also outperformed FHA loans in Texas.…”
Section: Overview Of the City Of Dallas Mapmentioning
confidence: 99%
“…An appropriate neighborhood definition is critical to studying the impacts on “neighbors.” Previous studies, such as Di, Ma, and Murdoch (2007), defined neighborhoods using the U.S. census block groups to examine the impact of MAP. Despite the convenient access to block group–level demographic information, the census boundaries tend to define areas that are too large.…”
Section: Impacts Of Map On Neighborhoodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the city's percentage of LMI households with severe housing cost burdens in 2000 was 23.1 percent, for those listed in the database, the average back-end ratio, or the ratio derived by dividing total monthly debt by monthly gross income, was 36 percent. Di, Ma, and Murdoch (2007) found that the mortgage default rate and foreclosure rate of MAP were lower than that of subprime loans in Texas-the likely alternative for LMI households. MAP loans also outperformed FHA loans in Texas.…”
Section: Overview Of the City Of Dallas Mapmentioning
confidence: 92%
“…Smith and Hevener (2005), Schwartz et al (2006) and Ellen et al (2007) found that place-based revitalization projects have significant positive spillover effects on the surrounding neighborhood. Di, Ma, and Murdoch (2007) analyzed the experience of Dallas Mortgage Assistance Program (MAP) participants and found no evidence of adverse impact of high concentration of MAP properties on block group median home values. However, their analysis is subject to the possible selection of MAP participants into block groups and the potential endogeneity of block group demographics.…”
Section: Introductionmentioning
confidence: 99%